A fully automatic tool for development of population pharmacokinetic models - Xiaomei Chen; Rikard Nordgren; Stella Belin; Alzahra Hamdan; Shijun Wang; Tianwu Yang; Zhe Huang; Simon J. Carter; Simon Buatois; João A. Abrantes; Andrew C. Hooker; Mats O. Karlsson (Wiley, 2024)
Abstract Population pharmacokinetic (PK) models are widely used to inform drug development by pharmaceutical companies and facilitate drug evaluation by regulatory agencies. Developing a population PK model is a multi‐step, challenging, and time‐consuming process involving iterative manual model fitting and evaluation. A tool for fully automatic model development (AMD) of common population PK models is presented here. The AMD tool is implemented in Pharmpy, a versatile open‐source library for pharmacometrics. It consists of different modules responsible for developing the different components of population PK models, including the structural model, the inter‐individual variability (IIV) model, the inter‐occasional variability (IOV) model, the residual unexplained variability (RUV) model, the covariate model, and the allometry model. The AMD tool was evaluated using 10 real PK datasets involving the structural, IIV, and RUV modules in three sequences. The different sequences yielded generally consistent structural models; however, there were variations in the results of the IIV and RUV models. The final models of the AMD tool showed lower Bayesian Information Criterion (BIC) values and similar visual predictive check plots compared with the available published models, indicating reasonable quality, in addition to reasonable run time. A similar conclusion was also drawn in a simulation study. The developed AMD tool serves as a promising tool for fast and fully automatic population PK model building with the potential to facilitate the use of modeling and simulation in drug development.